Temporary Import Tariffs, the Real Exchange Rate and the Current Account. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
In this paper a general equilibrium intertemporal model with optimizing consumers and producers is developed to analyze how the imposition of a temporary import tariff affects the path of real exchange rates and the current account. The model is completely real, and considers a small open economy that produces and consumes three goods each period. It is shown that, without imposing rigidities or adjustment costs, interesting paths for the equilibrium real exchange rate can be generated. In particular 'equilibrium overshooting' can be observed. Precise conditions under which a temporary import tariff will worsen the current account in period 1 are derived. Several ways in which the model can be extended are discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet